Restorative Justice Implementation In Bali Police Cybercrime Cases: Procedures, Barriers, And Digital Recovery - Putera, Bagus Muhamad Salim; Nahak, Simon; Rideng , I Wayan (Protection: Journal Of Land And Environmental Law, 2026)
This article examines how restorative justice is implemented in cybercrime cases handled by the Bali Regional Police's Cyber Directorate, with the dual aim of identifying operational barriers and formulating strengthening strategies. The analysis is anchored in concepts of criminal law and punishment, as well as the purposes of law—justice, legal certainty, and social utility—so that restorative outcomes can be assessed against principled thresholds rather than ad hoc compromise. The study employs a juridical-normative method complemented by empirical materials drawn from interviews, document analysis, and limited observation of case conferences and mediated settlements, alongside multi-year case data. The findings show uneven implementation that improves when case triage is disciplined and when a digital recovery toolkit—timely content removal, account restoration, verifiable restitution, public clarification, and guarantees of non-repetition—is applied. Key impediments include institutional formalism, technical features of cyber offending, the scarcity of specific operational guidelines, concerns about victims' rights and legal certainty, public misconceptions, and gaps in mediation and forensics capacity. The results suggest restorative justice should operate as a conditional instrument: prioritized where measurable recovery for victims is feasible and redirected to prosecution when public interest and deterrence predominate. Strengthened risk-based SOPs, targeted training, inclusive outreach, platform liaison, and victim-centered performance metrics are recommended to balance justice, certainty, and utility